Izhodišča za pripravo spletne oglaševalske akcije - Vukasović, Tina; Söke, Henrik (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The purpose of this paper was to study and present the background for search engine marketing, and on the basis of my findings, to run an actual advertising campaign on the Bing search engine. The article consists of two parts. In the first part of this article we'll show you the theoretical starting points of preparing an advertising campaign in the Bing search engine. We explore search engines in terms of how they work, how people are using them and present their market share data in the US. We also take a look of current and developing trends in online advertising. The empirical part presented in the second part of the paper was written using the inductive and deductive research methods, together with quantitative analysis, and my own findings and opinions. Among the most important findings of this research is the necessity of preparing well for the advertising campaign, the significance of writing effective advertising texts, using high converting landing pages, and the importance of analysis of obtained data.
Keywords: search engines; internet marketing; search engine marketing; Bing Ads; affiliate programs